REAKSI PASAR TERHADAP TINDAKAN PERATAAN LABA DENGAN MEKANISME GOOD CORPORATE GOVERNANCE SEBAGAI VARIABEL MODERASI (STUDI PERISTIWA PENGUMUMAM LABA PERUSAHAAN) (Jurnal Akuntansi (Media Riset Akuntansi & Keuangan), 2012)
This study aimed to determine whether the mechanism of Good Corporate Governance(GCG), in this case the managerial ownership, institutional ownership and audit committee,income smoothing actions affect relations with the market reaction to the earningsannouncement period. The populations of this study are all manufacturing companies listedon the Indonesia Stock Exchange in 2011. While the sample is selected menjadai 49companies manufacturing. Samples were selected through purposive sampling method withthe sample selection criteria. The dependent variable used is proxied by the market reactionComulative Abnormal Return (CAR). While independent variable is income smoothingmeasures and moderating variables used are institutional ownership, managerial ownershipand audit committee. Hypothesis testing is performed by multiple regression analysis. Basedon the analysis, this study failed to prove the third hypothesis because it is greater than thesignificance level alpha of 5% (0.05). All independent variables have no significant effect onthe market reaction.Keywords: market reaction, managerial ownership, institutional ownership, of the auditcommittee.